2018
DOI: 10.1161/jaha.117.008080
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Caregiver Determinants of Patient Quality of Life and Caregiver Strain in Left Ventricular Assist Device Therapy

Abstract: BackgroundAlthough current guidelines emphasize the importance of social support to the success of left ventricular assist device (LVAD) therapy, few studies examine the influence of the caregiver on patient outcomes or quantify the impact of LVAD caregiving on caregiver outcomes. The purpose of this analysis was to identify patient and caregiver determinants of patient quality of life (QOL) and caregiver strain in response to LVAD therapy.Methods and ResultsData on patients receiving LVAD therapy and their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 44 publications
2
48
0
Order By: Relevance
“…This result is consistent with other studies, especially in Asian countries that have similar norms [10]. Another study found that not only the type of the relationship but also its quality affects the caregiver's level of strain [23].…”
Section: Caregiver Burdensupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with other studies, especially in Asian countries that have similar norms [10]. Another study found that not only the type of the relationship but also its quality affects the caregiver's level of strain [23].…”
Section: Caregiver Burdensupporting
confidence: 91%
“…The novel aspect of this study is the relationship between cardiac patients' QoL and the caregiver burden due to the limited number of studies on this subject. It is noteworthy that the PLOS ONE burden increased when the patients' QoL increased; this is consistent with the study by Bidwell et al [23] in which they found that when the QoL of cardiac patients improved at one month post discharge after left ventricular assist device therapy, the caregiver burden was the highest. The same result was found in the meta-analysis study by Bidwell et al [34], which observed that improving the QoL of cardiac patients led to more physical and emotional strain on their caregivers and more time spent providing care for which they were unprepared, especially as most of them were young, female, and uneducated.…”
Section: Predictors Of Caregiver Burdensupporting
confidence: 90%
“…In brief, despite the improvements in emotional health, the illness denial defense mechanism increased when approaching discharge to home. This is not surprising considering that returning home may represent a threatening phase requiring to assume stronger personal responsibilities in order to manage the device and the several related lifestyle changes …”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, the left ventricular assistance device (LVAD), a modern electromedical circulatory used in patients with advanced heart failure, dramatically changed the life‐conditions of an increasing number of patients and consequently of their caregivers . In fact, the implanted device may have a significant impact on patients’ and caregivers’ lives, sometimes requiring them to cope with several adaptation challenges . The presence of emotional distress and psychological issues have been identified, providing evidence that these aspects need to be assessed for patients and caregivers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation